The Effectiveness of Planning Regulation to Curb Urban Sprawl. The Case of Striano (NA). - Russo, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Italy is facing an almost irreversible, extremely serious condition. A vital asset for humankind and the ecosystem, such as land, today suffers the negative effects of anthropogenic activities, first of all its uncontrolled and limitless consumption. Such transformation of landscapes and environments, due to the misuse of land, not only affects the Italian country, but it spills over its borders: across Europe, urban sprawl is threatening agricultural productivity and biodiversity, increasing the risk of flooding, reducing water resources and contributing to global warming (ISPRA 2012). The catastrophic impacts related to the spread of urban sprawl have made the identification of planning strategies capable of reducing the phenomenon essential. In Italy, many regions are trying to conform regulations and planning tools to control land use, and among them the Campania Region. To date, only few studies have evaluated the effectiveness of these tools in curbing the phenomenon (Anthony, 2004), to this end, the paper aims to assess the ability of Campania’s Planning regulations and tools in checking urban sprawl. The analysis was conducted in the town of Striano, within the complex urban conurbation of the Metropolitan Area of Naples, which can be considered an example of urban sprawl development pattern. In particular, a hypothesis of Area Action plan for Striano was developed on the basis of the measures imposed by Regional Law n. 16 of 2004 and the ones proposed by PTCP of Naples, then the potential outcomes achieved by the Plan were evaluated in terms of land use and density. The case study results show a disconnection between the current legislation and the new planning tools which are pending approval, therefore, the paper suggests the need to update Campania’s Planning legislation to the new guidelines, which are much more effective in terms of land protection.